2018
DOI: 10.1016/j.ijsolstr.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of matrix shear strength on the out-of-plane compressive strength of CFRP cross-ply laminates

Abstract: The failure mechanism of 'indirect tension' is explored for cross-ply IM7/8552 carbon fibre/epoxy laminates subjected to quasi-static, out-of-plane compressive loading. The sensitivity of compressive response to strain rate and to the state of cure is measured, motivated by the hypothesis that the out-of-plane compressive strength is sensitive to the matrix shear strength. A pressure-sensitive film is placed between specimen and loading platen, and reveals that a shear lag zone of reduced compressive traction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Attwood et al 9 used a high-speed camera to study the impact damage mechanism of laminates with back support, and found that fiber indirect tensile fracture is the main damage mode. Yu et al 10,11 studied the sensitivity of strain rate and curing state to the out-of-plane compression response of laminates. With the increase in the shear strength of the matrix, the through-the-thickness compressive performance of the laminated plate increases, and the sensitivity to strain rate decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Attwood et al 9 used a high-speed camera to study the impact damage mechanism of laminates with back support, and found that fiber indirect tensile fracture is the main damage mode. Yu et al 10,11 studied the sensitivity of strain rate and curing state to the out-of-plane compression response of laminates. With the increase in the shear strength of the matrix, the through-the-thickness compressive performance of the laminated plate increases, and the sensitivity to strain rate decreases.…”
Section: Introductionmentioning
confidence: 99%
“…If a strategy can be developed whereby CFRP fails by indirect tension rather than by shear plugging, then a major advance could be made in terms of its penetration resistance. Recently, it has been shown that the indirect tension mechanism can be activated in CFRP cross-ply laminates under quasi-static out-of-plane compressive loading [9], indentation loading [10], and ballistic impact loading [10]. The ballistic limit (i.e.…”
Section: Introductionmentioning
confidence: 99%